1993
DOI: 10.1007/bf02001462
|View full text |Cite
|
Sign up to set email alerts
|

Orbital pain and unruptured carotid-posterior communicating artery aneurysms: The role of sensory fibers of the third cranial nerve

Abstract: Intact aneurysms of the carotid siphon at the point of take-off of the posterior communicating artery may exhibit orbital pain, whether associated with oculomotor palsy or not as a warning symptom prior to rupture. In order to explain this symptom the hypothesis of a sensory pathway within the third cranial nerve, which is liable to compression by the enlarging aneurysm sac, has been investigated. Data from human autopsy material show evidence of sensory ganglion cells within the rootlets of the oculomotor ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 9 publications
4
38
0
Order By: Relevance
“…9 Compression of the pain sensory afferent fibers, which are recruited from the ophthalmic division of the trigeminal nerve and which lie within the periphery of the oculomotor nerve, causes ipsilateral orbitofacial pain. 10 Compressive lesions of the cavernous sinus may lead to localized oculomotor or abducens CN dysfunction and Horner syndrome. 11 Evolution of ocular motor nerve (third, fourth, and sixth) paresis after endovascular therapy has been reported in the literature: Beyond sporadic reports with ONP resolution after coiling of PcomA aneurysms, 12 a literature review concerning series including Ն3 aneurysms revealed a mean rate of 46.6% complete recovery after endovascular treatment of 118 (55/118) aneurysms that caused ophthalmoplegia (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…9 Compression of the pain sensory afferent fibers, which are recruited from the ophthalmic division of the trigeminal nerve and which lie within the periphery of the oculomotor nerve, causes ipsilateral orbitofacial pain. 10 Compressive lesions of the cavernous sinus may lead to localized oculomotor or abducens CN dysfunction and Horner syndrome. 11 Evolution of ocular motor nerve (third, fourth, and sixth) paresis after endovascular therapy has been reported in the literature: Beyond sporadic reports with ONP resolution after coiling of PcomA aneurysms, 12 a literature review concerning series including Ն3 aneurysms revealed a mean rate of 46.6% complete recovery after endovascular treatment of 118 (55/118) aneurysms that caused ophthalmoplegia (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, oculomotor palsy, when in association with ipsilateral orbitofacial pain, strongly indicates impending aneurysmal rupture. Compression of pain sensory afferent fibres of the ophthalmic division of the f f trigeminal nerve present in the third cranial nerve by the aneurysm is alleged by some as the cause of the orbital headache [25]. In this regard, Berardinelli et al [26] identified unmyelinated fibres in the oculomotor, trochlear and abducens nerves, and suggested that they are sensory in nature and are involved in the transport of pain signals arising from the trigeminal territory.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7]10,13) Orbital pain or headache sometimes proceed to oculomotor nerve palsy which frequently involves the pupil. The external ocular movement is partly disturbed or the eye position becomes exotropic resulting in double vision.…”
Section: Discussionmentioning
confidence: 99%